Developing process and product innovation through internal and external knowledge sources in manufacturing Malaysian firms: the role of absorptive capacity. Issue 5 (4th May 2020) - Ramayah, T.; Soto-Acosta, Pedro; Kheng, Khoo Kah; Mahmud, Imran
Abstract : Purpose: Firms' knowledge-processing capabilities have a central role in achieving innovation performance and competitive advantage. Absorptive capacity capabilities and innovation are viewed as essential for enterprise success. Absorptive capacity is deemed as a highly important organizational capability to recognize value and assimilate both external and internal knowledge in order to enhance firm innovation. The aim of this study is to determine if innovation performance can be improved through absorptive capacity (knowledge acquisition, dissemination and utilization), when it is supported by internal (firm experience) and external knowledge sources (R&D cooperation and contracted R&D). Design/methodology/approach: A quantitative methodology based on employing a structured questionnaire was used for data collection. The proposed research model and its associated hypotheses are tested by using Partial Least Squares (PLS) structural equation modelling (SEM) on a data set of 248 manufacturing companies located in the Northern Region of Malaysia. Findings: Results showed that firms' experience is significantly related to absorptive capacity, while for R&D cooperation and contracted R&D findings were mixed. In addition, absorptive capacity was found as a strong predictor of innovation performance. Originality/value: One of the defining features of competition in many industries has been the extremely rapid pace of technological change, marked by a continuous stream of innovations. Manufacturing firms, therefore, face the challenge of nurturing existing knowledge and developing novel knowledge in order to create new business opportunities. This study makes valuable contributions with regard to understanding the behavioural of manufacturing firms towards process and product innovation.